PRE-SERVICE TEACHERS' NEEDS: A PANACEA FOR COMPETENT SCHOOLING PREPARATION IN NIGERIA - Muhammad Alhaji Ibrahim (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
Teacher Education training has played a central role in the training of individuals, who are responsible for impacting knowledge, behavior, attitude, and skills, in order to ensure better productivity and efficiency in the society. The main objectives of this study are to identify preservice teachers’ needs and what component of teaching knowledge they require? How could we satisfied their needs? And how do we ensure their needs are adequately provided for effective classroom instruction? The finding of this study has shown that the inability of many teacher education training in satisfying preservice teachers needs has made it difficult for them to possess the require subject matter knowledge and skills for effective classroom instruction. The study has identify two preservice teachers’ needs (i.e. learning needs and teaching needs). The need are further categorized into cognitive needs, emotional needs and physical needs. Therefore, it is pertinent for the training to bridge the gap between the current practice in the training and the desired practice in order to groom competent school teachers and achieve the set objective of the training. It is recommended that the training should examine relevant strategies adopted in the training, and adjusted to current realities of needs of the preservice teachers to ensure that the training is appropriately managed to achieve the set objectives of the training Keyword: Preservice teachers; teaching needs; competent school teachers